The development of the idea of limbo in the Middle Ages - Beiting, C; Beiting, Christopher (1997)
﻿ The medieval period witnessed many attempts at organization, of both the mundane and sacred spheres. The otherworldy realms of heaven and hell are familiar to the modern reader, as is purgatory, but it was during the middle ages that the existence of another realm, limbo, was posited. This realm had its beginnings in questions of Christology and the extent to which Christian salvation could or could not be extended to non-Christian peoples. Its development was also shaped by questions of infant baptism, and the fate of those infants who died lacking this baptism. By the thirteenth century, it becomes more proper to speak of "the limbos", as the idea of limbo is split into two realms: the limbo of the Fathers (limbus patrum), wherein were placed the notable figures of the Old Testament, and the limbo of children (limbus puerorum). wherein were placed unbaptized infants of the Christian era. This thesis examines the development of the idea of limbo, concentrating primarily on works of speculative theology. It begins with the roots of the idea of limbo to be found in the writings of Augustine of Hippo and in the apocryphal Christian work, the Gospel of Nicodemus. From there, the questions of original sin, divine redemption, and baptism which shape the development of the idea of limbo are examined in the writings of several influential twelfth-century authors, including Anselm of Canterbury, Peter Abelard, Bernard of Clairvaux, and Peter Lombard. The earliest uses of the term "limbo" are examined in the works of William of Auvergne and William of Auxerre, and the full theology of limbo is considered in the works of the high scholastic writers Alexander of Hales, Albertus Magnus, Thomas Aquinas, and Bonaventure. Finally, the thesis concludes with a fusion of theology and art in an examination of the unique depiction of limbo in Dante's Divine Comedy.